Lessons from the London Initiative Zone Educational Incentives funding: associations between practice characteristics, funding, and courses undertaken. - Hull, SA; Tissier, J; Moser, K; Derrett, C; Carter, Y; Eldridge, S (2000)
BACKGROUND: Following the Tomlinson report of 1992, London Initiative Zone Educational Incentives (LIZEI) funding was introduced for a three-year period to improve recruitment, retention, and educational opportunities for general practitioners working within inner London. AIM: To test the hypothesis that general practices that show evidence of good organisation achieved better access to LIZEI funding than less organised practices. METHOD: Observational practice-based study involving all 164 general practices in EAst London and the City Health Authority during the first two years of the scheme, April 1995 to March 1997. RESULTS: Univariate analysis showed that higher levels of LIZEI funding were associated with practices where there was evidence of good organisation, including higher targets for cervical cytology screening and immunisation rates for under two-year-olds, better asthma prescribing, and training status. Using ten practice and population explanatory variables, multiple regression models were developed for fundholding and non-fundholding practices. Among non-fundholding practices, the asthma prescribing ratio was the variable with the greatest predictive value, explaining 14.7% of the variation in LIZEI funding between practices. Strong positive associations existed between taking further degrees and diplomas, practice size, training, and non-fundholding status. CONCLUSION: Larger practices, training practices, and those that demonstrated aspects of good practice organisation gained more LIZEI funding: an example of the 'inverse funding law'. Practices within a multifund, based in the Newham locality, gained LIZEI funding regardless of practice organisation. Networks of practices, and, potentially, primary care groups, have a role in equalising the opportunities for education and development between practices in east London.